The strategic linkage between organizational context and information systems success : A study on the Malaysian MSC status companies - Zakariya Belkhamza (2011)
In the modern world, and because the organizational forms are changing, there is a need for a deeper investigation on the linkage between organization context and information system in the organization. The statement that the information system did not fit the organizational culture is often part of the explanation of why particular information system encountered unanticipated resistance and never met expectations. This study aims to provide a fundamental framework for a new concept of the linkage between organizational context and information systems success. This study explores the concept of organizational context dimensions suggested by Ghoshal and Bartlett (1994), stretch, trust, support and discipline, as the shapers of organizational culture, and relates them to the information systems research, focusing on the information systems success as represented by system performance, information effectiveness and service performance, particularly investigating the role of the managerial action affecting this linkage. To investigate this problem, the study first develops instrument to measure the organizational context constructs, validates them and then uses partial least squares (PLS) techniques to test the hypothesized model. Data used for this research was collected from a sample of 317 MSC status companies in Malaysia. The results show good support for the theorized model. Except trust, the organizational context is proven to be major factor for the success of information systems in the organization, especially when the organizational act ambidextrously within the information systems context. The study ends by introducing a four-stage sociotechnical model coined as System Behavioral Success Model (SBS), which describes how the behavioral context of an IT organization led by their IT executives would lead to the success of the information systems function.